Measurement of wakefields in plasma by a probing electron beam - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Uskov, V.V. (Вопросы атомной науки и техники, 2007)
The device for measuring intensity of wakefield, excited in plasma by a sequence of bunches of relativistic electrons is presented. Field amplitude is determined by measuring deflection of a probing electron beam (10 keV, 50 mА, of 1 mm diameter), which is injected perpendicularly to a direction of bunches movement. Results of measurement of focusing radial wakefield excited in plasma of density 5×10¹¹ cm⁻³ by a sequence of needle electron bunches (each bunch of length 10 mm, diameter 1.5 mm, energy 14 МeV, 2×10⁹ electrons in bunch, number of bunches 1500) are given. The measured radial wakefield strength was 2.5 kV/cm.